Florida Invader: Burmese Python - Steve A. Johnson; Monica E. McGarrity (EDIS)
WEC288, a 2-page illustrated fact sheet by Steve Johnson and Monica McGarrity, is part of the Florida Invaders series. It provides key information and illustrations for identifying and reporting sightings of this large nocturnal predator that is native to Southeast Asia and is now established and breeding in Florida and Puerto Rico. Published by the UF Department of Wildlife Ecology and Conservation, September 2010.